A review of low carbon fuel policies: Principles, program status and future directions. (October 2016) - Yeh, Sonia; Witcover, Julie; Lade, Gabriel E.; Sperling, Daniel
Abstract: A low carbon fuel standard (LCFS) is a market-based policy that specifies declining standards for the average lifecycle fuel carbon intensity (AFCI) of transportation fuels sold in a region. This paper: (i) compares transportation fuel carbon policies in terms of their economic efficiency, fuel price impacts, greenhouse gas emission reductions, and incentives for innovation; (ii) discusses key regulatory design features of LCFS policies; and (iii) provides an update on the implementation status of LCFS policies in California, the European Union, British Columbia, and Oregon. The economics literature finds that an intensity standard implicitly taxes emissions and subsidizes output. The output subsidy results in an intensity standard being inferior to a carbon tax in a first-best world, although the inefficiency can be corrected with a properly designed consumption tax (or mitigated by a properly designed carbon tax or cap-and-trade program). In California, from 2011 to 2015 the share of alternative fuels in the regulated transportation fuels pool increased by 30%, and the reported AFCI of all alternative fuels declined 21%. LCFS credit prices have varied considerably, rising to above $100/credit in the first half of 2016. LCFS programs in other jurisdictions share many features with California's, but have distinct provisions as well. Highlights: LCFS is a market-based policy that sets standards for carbon intensity of fuels. We compare efficiency, price impacts, GHG emissions, and innovation of C policies. In California, reported carbon intensity of alternative fuels declined 21% 2011–2015. LCFS credit prices have varied considerably, rising to above $100/credit in the first half of 2016. Other LCFS programs share many features with CA's and have distinct provisions.